Setting the Stage: Measure Selection, Coordination, and Data Collection for a National Self-Management Initiative - Kulinski, Kristie P.; Boutaugh, Michele; Smith, Matthew Lee; Ory, Marcia G.; Lorig, Kate (Frontiers in Public Health, 2015)
.